Pengaruh Opini Auditor Dan Jumlah Komite Audit Terhadap Audit Delay Dengan Auditor Switching Sebagai Variabel Intervening - Dila Anindya Irene; Muhammad Salman; Tuti Meutia (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This study aims to find out the influence of auditor's opinion and the number of audit Committees on Audit delay and Auditor switching as intervening variables in trading, services and investment companies listed in the Sharia stock index in 2011-2020. The population of this study was 89 trading,services and investment companies listed on the Sharia stock index in 2011-2022. The sampling method used was purposive sampling method, so that 9 sample companies were obtained. The data analysis method used is classical assumption test, path analysis test and sobel test using SPSS (Statistical Package for the Social Science) as an analysis tool. The results of this study stated that the auditor's opinion and the number of audit committees did not significantly affect the auditor switching. Auditor switching, auditor opinion and number of audit Committee did not significantly affect audit delay. Switching auditors cannot mediate the effect of auditor's opinion and the number of audit Committees on audit delay. The limitation of this study is the lack of the latest references and the latest theories about Auditor switching and audit delay. Suggestions from this study that investors pay more attention to the condition of the company compared with the auditor's opinion. Because it does not mean if the opinion given by the auditor other than Unqualified the company has a bad reputation because many other aspects can be seen and assessed from the company's performance other than the auditor's opinion.